Buccoo Bay, Tobago, B.W.I. - Parker, J. (The Tourist Exhibtion Board of Trinidad and Tobago; Printed by Robert Maclehose, Scotland., 2011)
This postcard shows Buccoo Bay in Tobago. This card is addressed to Mr. and Mrs. Richard B. Pomeroy of New York, United States of America.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Art--Trinidad and Tobago